Um diálogo entre culturas a partir do texto dramático Ñuke - Assis Benevenuto Vidigal (2021)
This work is dedicated to a critical reading of the dramatic text Ñuke, by the Mapuche Chilean playwright David Arancibia Urzúa, as a first step towards developing a cultural dialogue with the Brazilian context. Therefore, it was necessary to carry out a historical and political study from the period of the European invasion of the Americas, fifteenth century, widely spread as the "discovery" of the Americas, through governmental transformations, independence and formation of nation-states, until the present day. We rely on geopolitical maps, contemporary images that symbolize the secular struggle and authors who recover the historical and cultural narratives of the native peoples, who resisted to an erasure and destruction project of the colonizing power, as a way to apprehend this whole context under another point of view. Afterwards, we present the author and his work in a dramatic analysis of the text, comparing it with the theatre production performed by KIMVN Group and with the first version of the text published in Chile, at 2013. We explain some terms in the Mapudungun language, used in dramaturgy, that reveal aspects of Mapuche culture and elevate Arancibia's dramaturgy to the status of political theater. Finally, in dialogue with image theorists, such as Jacques Rancière and Georges Didi-Huberman, we analyze some critical images present in the work.